Dear Justice League : a graphic novel - Northrop, Michael (DC Comics, 2019)
While the heroes of the Justice League are out saving the good citizens of the world, some of their biggest middle grade fans write letters and online messages to them asking important questions--such as if Superman has ever made a mistake or if Batman has ever felt like a new kid at school. Their answers are honest and inspiring for the kids.